Podložniška politična kultura v postkomunističnih družbah - Kirbiš, Andrej (Družboslovne razprave, 2011)
The present study examined several measures of political culture among 2,178 social science students (M age = 19.8 years, SD = 1.89) in eight post-Yugoslaventities. The aggregate-level results indicate that socio-economically less developed environments had higher average levels of subject political culture, which is characterised by authoritarianism, general traditionalism, traditional gender role attitudes, state paternalism and general distrust. The only exception from this tendency was the measure of economic egalitarianism, where between-country differences were not significant. The authors demonstrate that, nearly two decades after the dissolution of Yugoslavia, some of the same value differences are still found in its successor territories. They conclude that the process of democratic consolidation is far from over in post-Yugoslav entities and that Slovenia comes closest to achieving that goal in the political-cultural context.
Keywords: Political culture; Politična kultura; Politične vrednote; Political values; Postcommunism; Postkomunizem; Democratization; Demokratizacija; Youth; Mladina; Yugoslavia; Jugoslavija